Bioelectrical controls of morphogenesis: from ancient mechanisms of cell coordination to biomedical opportunities. (August 2019) - Whited, Jessica L; Levin, Michael
Abstract : Cell-to-cell communication is a cornerstone of multicellular existence. The ancient mechanism of sharing information between cells using the conductance of ions across cell membranes and the propagation of electrical signals through tissue space is a powerful means of efficiently controlling cell decisions and behaviors. Our understanding of how cells use changes in 'bioelectrical' signals to elicit systems-level responses has dramatically improved in recent years. We are now in a position to not just describe these changes, but to also predictively alter them to learn more about their importance for developmental biology and regenerative medicine. Recent work is helping researchers construct a more integrative view of how these simple controls can orchestrate downstream changes in protein signaling pathways and gene regulatory networks. In this review, we highlight experiments and analyses that have led to new insights in bioelectrical controls, specifically as key modulators of complex pattern formation and tissue regeneration. We also discuss opportunities for the development of new therapeutic approaches in regenerative medicine applications by exploiting this fundamental biological phenomenon.